Silvia: a flexible system for integrated plantation management - Vallejo, A.; Kanninen, M.; Montero, M.; Viquez, E. (Scientific Publishers (India), 2006)
Silvia-Forest Management System is a computer application designed to help managers and technicians in the sustainable management of forest plantations. Silvia version 2 includes a plantations database, an equations database, and modules to simulate future grwoth and yield, process inventory data, and carry out financial analyses. Map layers in several GIS formats can be linked to Silvia to render several types thematic maps. Simulations can be run with sets of equations provided by Silvia or by the user based on growth studies. Silvia can be used for projects of different sizes, from small farms to multinational forest companies without any limitation regarding the number of stands, species, or geographical units included in the project.